(NsOWREMENNYE RUSSKIE GOWORY (B:s [(NsBORNIK STATEJ(B] /s - (NaZARH(B, (N`LIQ sEMENOWNAs ((NmOSKWA (B:s (NnAUKA(B,s, 1991)
(NbIBLIOGR(B. (NW KONCE ST(B. (NbIBLIOGR(B. (NW PRIME^(B. (NW KONCE ST(B.s
(Nan sssr(B, (NiN(B-(NT RUS(B. (NQZ(B.s
Keywords: (NrUSSKIJ QZYKs -- (NdIALEKTYs